Ideals and Principles of Common Wellbeing under Social and Humanistic Paradigm; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 19 : Lifelong Wellbeing in the World (WELLSO 2016) - Kornienko A. A. Alla Alexandrovna; Kvesko S. B. Svetlana; Kornienko A. A. Anna Anatolievna; Kabanova N. N. Natalia Nikolaevna; Nikitina Yu. A. Yulia Anatolyevna (2017, 2017)
Title screen